2021
DOI: 10.36311/jhgd.v31.12605
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality and lethality in the State of Pará, legal Amazon, Brazil

Abstract: Introduction: the growth of coronavirus indices in the North region highlights the region’s historical social inequalities and the problems in accessing citizenship. Objective: to analyze the mortality and lethality of COVID-19 in the state of Pará, Brazil. Methods: this is an ecological study with a time series design of secondary data. All registered cases and deaths reported by COVID-19 in the period from March 2020 to June 2021, in the state of Pará, Brazil, were considered. The incidence and mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Other researchers demonstrated that the studied health indicators presented similar serial correlation parameters in other Brazilian states 15,16 . Some years of mortality, lethality and incidence indicators did not show statistical significance during the analysis of the temporal trend, however the values presented are important for planning at the state level to propose measures to reduce or stabilize the number of cases and deaths.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Other researchers demonstrated that the studied health indicators presented similar serial correlation parameters in other Brazilian states 15,16 . Some years of mortality, lethality and incidence indicators did not show statistical significance during the analysis of the temporal trend, however the values presented are important for planning at the state level to propose measures to reduce or stabilize the number of cases and deaths.…”
Section: Discussionmentioning
confidence: 53%
“…An uncontrolled dissemination is observed, a behavior that was related to the pandemic response model 18 . And it can be justified by access to health care, socioeconomic and demographic conditions, and factors intrinsic to the population, such as age, lifestyle, comorbidities, among others 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The state of Acre presents a complex scenario influenced by multiple variables affecting the pandemic and the spread of COVID-19 [ 7 , 50 ], leading to numerous challenges impacting incidence, mortality, and lethality rates. Among its 22 municipalities, 14 are categorized as rural [ 11 ], where rivers serve as crucial transportation routes for people and goods, and in some areas, they represent the only form of access.…”
Section: Discussionmentioning
confidence: 99%
“…The seven states in the North region collectively accounted for 11.9% of the country's total COVID-19 cases. Among these, the municipalities with the highest number of new cases were Manaus/AM (2,026), Belém/PA (1,686), and Boa Vista/RR (1,328). In July 2020, Pará held the fourth position with one of the highest COVID-19 case counts nationally.…”
Section: Discussionmentioning
confidence: 99%